2010
DOI: 10.1038/nature09609
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genomics identifies LMO1 as a neuroblastoma oncogene

Abstract: Neuroblastoma is a childhood cancer of the sympathetic nervous system that accounts for approximately 10% of all paediatric oncology deaths1,2. To identify genetic risk factors for neuroblastoma, we performed a genome-wide association study (GWAS) on 2,251 patients and 6,097 control subjects of European ancestry from four case series. Here we report a significant association within LIM domain only 1 (LMO1) at 11p15.4 (rs110419, combined P = 5.2 × 10−16, odds ratio of risk allele = 1.34 (95% confidence interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
313
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(327 citation statements)
references
References 19 publications
(23 reference statements)
11
313
2
1
Order By: Relevance
“…Two other LIM-only proteins, LMO1 and LMO4, are also important determinants of cell cycle progression in neuroblastoma (23) and in breast cancer associated with genomic instability (22), respectively, suggesting that the mechanism(s) described here may be extended to these proteins. Emerging evidence indicates that oncogenes, such as c-MYC or HOXD13, can be part of nontranscriptional complexes involved in DNA replication (54,57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other LIM-only proteins, LMO1 and LMO4, are also important determinants of cell cycle progression in neuroblastoma (23) and in breast cancer associated with genomic instability (22), respectively, suggesting that the mechanism(s) described here may be extended to these proteins. Emerging evidence indicates that oncogenes, such as c-MYC or HOXD13, can be part of nontranscriptional complexes involved in DNA replication (54,57).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, LMO2 is misexpressed in the T lineage, where it is normally absent. In addition, LMO proteins are frequently deregulated in breast cancers (22) and neuroblastomas (23), pointing to their importance in cell transformation. In particular, in patients who eventually developed T-ALL associated with LMO2 activation after gene therapy, T-cell hyperproliferation was observed early during the preleukemic stage (19).…”
mentioning
confidence: 99%
“…Through a genomewide association study (GWAS) of sporadic neuroblastoma, we have reported common single nucleotide polymorphisms (SNPs) associated with neuroblastoma susceptibility at CASC15 4, BARD1 5, LMO1 6, DUSP12 7, HSD17B12 7, DDX4/IL31RA 7, HACE1 8 and LIN28B 8 loci. Importantly, many of these GWAS‐identified genes have been shown to be key factors in both initiating and sustaining tumorigenesis 6, 8, 9, 10, 11. These results suggest that neuroblastoma tumorigenesis could be the result of multiple genetic alterations and that these variants can also influence the clinical outcome of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have also identified additional germline genetic variants in neuroblastoma patients, including single-nucleotide polymorphisms in LIN28B, BARD1, and LMO1, among others [26][27][28][29] as well as other polymorphisms in other chromosomal regions yet to be fully characterized [30,31]. These polymorphisms occur relatively frequently in the general population and may contribute to the development of sporadic neuroblastoma, although the functional roles of these germline variants and other somatic alterations remain to be elucidated.…”
Section: Epidemiology and Geneticsmentioning
confidence: 99%